Cytotoxic secondary metabolites isolated from Penicillium sp. YT2019-3321, an endophytic fungus derived from Lonicera Japonica - Weng, Wenya; Jiang, Shicui; Sun, Chuchu; Pan, Xiaofu; Xian, Li; Lu, Xuemian; Zhang, Chi (Frontiers in Microbiology, 2022)
Chemical survey on Penicillium sp. YT2019-3321, an endophytic fungus derived from traditional Chinese medicine Lonicera Japonica, resulted in the isolation of eight structurally diversified secondary metabolites, including two previously unreported polyketides, named (±)-chrysoalide B (1) and penicidone E (2). The chemical structures of the isolated compounds were established by a correlative interpretation of HRESIMS and NMR spectroscopic data. The optical resolution of (±)-1 by chiral HPLC yielded individual enantiomers (+)-1 and (−)-1, and their stereochemistry were solved by X-ray diffraction crystallography, respectively. Compound 2 possessed the γ-pyridone nucleus, which is rarely found in natural products. Cytotoxic assay revealed that the new compound 2 significantly induced apoptosis of human pancreatic tumor cells (PATU8988T), characterized by the morphologies abnormity, the reduction of cell number, the upregulation of proportion of apoptotic cells, and the ratio of Bcl-2 to Bax. Our study demonstrates that fungal secondary metabolites may have important significance in the discovery of drug leads.